Access to mifepristone, misoprostol, and contraceptive medicines in eight countries in the Eastern Mediterranean Region: descriptive analyses of country-level assessments - Mohamed Afifi; Nilmini Hemachandra; Qais Sikandar; Rana Hajjeh; Ulrika Rehnström Loi; Laurence Läser; Dima Qato; Zahir Sidiqui Abdul; Paata Chikvaidze; Raghad Abdul Redha Abbas; Khalid Al-Kinani; Hanan Hasan; et al. (BMC, 2024)
Abstract Background Despite their importance in reducing maternal mortality, information on access to Mifepristone, Misoprostol, and contraceptive medicines in the Eastern Mediterranean Region is limited. Methods A standardized assessment tool measuring access to Mifepristone, Misoprostol, and contraceptive medicines included in the WHO essential medicines list (EML) was implemented in eight countries in the Eastern Mediterranean Region (Afghanistan, Iraq, Lebanon, Libya, Morocco, Palestine, Pakistan, and Somalia) between 2020-2021. The assessment focused on five access measures: 1) the inclusion of medicines in national family planning guidelines; 2) inclusion of medicines in comprehensive abortion care guidelines; 3) inclusion of medicines on national essential medicines lists; 4) medicines registration; and 5) procurement and forecasting of Mifepristone, Misoprostol, and contraceptive medicines. A descriptive analysis of findings from these eight national assessments was conducted. Results Only Lebanon and Pakistan included all 12 contraceptives that are enlisted in the WHO-EML within their national family planning guidelines. Only Afghanistan and Lebanon included mifepristone and mifepristone-misoprostol combination in post-abortion care guidelines, but these medicines were not included in their national EMLs. Libya and Somalia lacked a national regulatory authority for medicines registration. Most contraceptives included on the national EMLs for Lebanon, Morocco and Pakistan were registered. Misoprostol was included on the EMLs-and registered-in six countries (Afghanistan, Iraq, Lebanon, Morocco, Palestine, and Pakistan). However, only three countries procured misoprostol (Iraq, Morocco, and Somalia). Conclusion These findings can guide efforts aimed at improving the availability of Mifepristone, Misoprostol, and contraceptive medicines in the Eastern Mediterranean Region. Opportunities include expanding national EMLs to include more options for Mifepristone, Misoprostol, and contraceptive medicines and strengthening the registration and procurement systems to ensure these medicines' availability were permitted under national law and where culturally acceptable.